The Effect of Digital Financial Literacy on Personal Financial Management Behavior among Generation Z: The Mediating Role of Lifestyle - Maya Oktaviana; Adhitya Yoga Prasetya (Al Dzahab, 2026)
Purpose: This study aims to investigate the role of digital financial literacy in shaping personal financial management behavior among Generation Z, while explicitly examining whether lifestyle acts as a mediating mechanism that strengthens or weakens this relationship in the context of increasing financial digitalization. Design/Methodology/Approach: A quantitative approach was employed using a survey of 420 Generation Z respondents aged 18–27 years in Gubug District. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to evaluate both direct and indirect relationships among variables. Findings: The results indicate that digital financial literacy has a positive and significant effect on personal financial management behavior. Lifestyle, however, has a significant negative effect on financial behavior and does not mediate the relationship between digital financial literacy and financial management behavior. These findings suggest that while digital financial literacy plays a central role in shaping financial behavior, lifestyle tends to weaken prudent financial practices. Research Implications: This study highlights the importance of strengthening digital financial literacy as a key driver of responsible financial behavior among Generation Z. Policymakers and educators are encouraged to promote inclusive and sustainable financial education programs, particularly amid rapid digitalization.